2020
DOI: 10.3390/pharmaceutics12090896
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Non-Viral Gene Modification of Mesenchymal Stromal Cells from Umbilical Cord Wharton’s Jelly with Polyethylenimine

Abstract: Mesenchymal stromal cells (MSC) derived from human umbilical cord Wharton’s jelly (WJ) have a wide therapeutic potential in cell therapy and tissue engineering because of their multipotential capacity, which can be reinforced through gene therapy in order to modulate specific responses. However, reported methodologies to transfect WJ-MSC using cationic polymers are scarce. Here, WJ-MSC were transfected using 25 kDa branched- polyethylenimine (PEI) and a DNA plasmid encoding GFP. PEI/plasmid complexes were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
3
1
Order By: Relevance
“…For instance, Ramos-Murillo et al reported 15.3 ± 8.6% transfection efficiency using bPEI 25 kDa in MSCs isolated from Umbilical Cord Wharton's Jelly. Interestingly, the viability of MSCs treated with PEI in their study was similarly reduced, comparable to our observations with the same concentration of PEI [32]. According to MTT assays in the present work, treatment with GO-PEI reduces the viability of MSC and Calu-3 cells by almost 25%, which are the most declining viability rates among the other studied cell types.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Ramos-Murillo et al reported 15.3 ± 8.6% transfection efficiency using bPEI 25 kDa in MSCs isolated from Umbilical Cord Wharton's Jelly. Interestingly, the viability of MSCs treated with PEI in their study was similarly reduced, comparable to our observations with the same concentration of PEI [32]. According to MTT assays in the present work, treatment with GO-PEI reduces the viability of MSC and Calu-3 cells by almost 25%, which are the most declining viability rates among the other studied cell types.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, GET* N/P 8 nanoparticles elicited the highest transfection efficiency in MSCs in 2D, significantly more so than unmodified GET and GET* N/P 6, and was also higher than the GET* N/P 11 group. This contrasts with similar optimisation studies in MSCs, where increasing N/P ratio tends to correlate with increased transfection efficiency [58,59]. One potential hypothesis to explain this result is that the increased positive charge conferred on GET* N/P 11 particles as a result of an increased proportion of FLH to FLR causes a more pronounced 'proton-sponge' effect and subsequently less viable cells can be transfected.…”
Section: Discussioncontrasting
confidence: 62%
“…As there is no genome integration, transgene expression can be reduced or lost post-cryopreservation [19]. Additionally, transfection reagents may compromise the integrity of cell membrane, raising concerns over the possibility of reduced cell viability during cryopreservation [20,21]. Metabolic burden imposed by significant exogenously expressed gene load can have detrimental effects [22], rendering the cells to be more vulnerable to the freezing and thawing process.…”
Section: Introductionmentioning
confidence: 99%